A Systematic Literature Review of Islamophobia on Media: Trends, Factors, and Stereotypes - Yudi Wili Tama; Siti Drivoka Sulistyaningrum (Indonesian Journal of Religion and Society, 2023)
Islamophobia is a concept that includes various types of discrimination against Muslims and their followers.This study explores trends in previous research on Islamophobia between 2013 and 2022, focusing on factors that contribute to Islamophobia in the media and prevalent stereotypes. A systematic literature review was conducted, involving the identification, evaluation, interpretation and analysis of relevant studies. The study found that Islamophobia in the media has gained significant attention and requires further investigation to understand current trends and develop solutions. Factors associated with Islamophobia include negative portrayal, structural bias, and a lack of understanding of Islam, which contributes to anti-Muslim sentiment. The study also identified stereotypes, such as Muslims being suspected of attacks, seen as a societal threat, labeled as "other," and women wearing headscarves being stigmatized as religious fanatics. Addressing Islamophobia in the media is crucial, and recognizing these contributing factors and stereotypes can help challenge biases and promote inclusivity in society